Sungai Wampu, Pendukung Kehidupan Pemukim Bukit Kerang - Taufiqurrahman Setiawan (Berkala Arkeologi Sangkhakala, 2008)
AbstractAs one of an ancient river in north Sumatera, the Wampu river has taken an important part in supporting a settlement area in Kitchen Midden on 5000--7000 BP.